Comparative analysis of the usage of concept "hospitality" in the phraseological units of English, Russian and Uzbek languages on the basis of the English translation of the novel “Silence” by S.Ahmad - Eshkuvvatovna, Kholmuradova Leyla; Tuychievna, Maya Sultanova; Furkatovna, Sharofova Diyora; qizi, Mamarizaeva Farangiz Zohidjon (Linguistics and Culture Review, 2021)
At present, in connection with globalization, the language is especially interested in cross-cultural understanding. Today, the interest in the study of original and translations of the text "Silence" in the world literary process is attracting the attention of orientalists and translators around the world. The scientific study of the content and phrase logical aspects of the novel "Silence" by world scholars, such as the creative personality, the writer's creative method, artistic skills, allows to identify and evaluate the features of the development of literature. According to structure of phrases, a phrase is a lexical unit that is equivalent to a sentence, semantically whole, has a generalized meaning, is not created in the speech process, but is ready to be introduced into the speech. According to the linguist Mamatov, phrases are a separate unit of language, which, according to their structure, is a free connection or equivalent to a sentence, fully or partially semantically reconstructed figurative, stable phrases. Phrases are specific figurative expressions of people's conclusions based on observation of life events, assessment of acceptable and unacceptable actions in society, generalization of life experiences. Writers are often not content to select and use phrases appropriate to the purpose of the image.